A Study on How to Master Japanese Numbers in Oral Conversation Using Japanese Inazuma Software - Mohd Iszuani, Mohd Hassan (2017)
The main objective of the study was to identify suitable sentence patterns in Japanese using numbers taken from the latest materials obtained from a recent course attended at the Japanese Language Institute at Urawa, Saitama, Japan. Participants in the present study were UMP engineering undergraduates who were required to take Japanese language course by their faculty. This research employed the quantitative methodology. A total of 120 UMP students who took compulsory Japanese language course were tested. The analysis applied interactional theory (Bloomfield, 1970; Halliday, 1973) in which measurement was based on the percentage of students who successfully used Japanese numbers in the recorded drama role-play. According from analysis, 60% students has problem for mastery of Japanese numbers in oral convers. Consequently, this research produced the new Japanese Inazuma software which has been used as a model for Japanese language multimedia learning at University Malaysia Pahang (UMP). By using this new software, students were able to apply their mastery of Japanese numbers in oral conversation. It is anticipated that the study will be useful in promoting the use of multimedia in the teaching and learning of foreign language not only among students at UMP or public universities but also at other institutions in Malaysia.